SONGS HELPED THEM LEARN THE ENGLISH CONNECTED SPEECH - Tono Suwartono; Puspita Mayaratri (Pusat Pengembangan Bahasa IAIN Tulungagung, 2019)
In the previous years, the students at the place where the present study was conducted were taught the English connected speech through drill. This used to bring about students’ poor attitudes and unsatisfactory achievement. This study was aimed at examining if selected songs would improve the students’ connected speech performance. Nonequivalent Control Group Design was used in this experimental study. It involved six intact groups of students attending Pronunciation course – three were randomly assigned to the experimental group and the remaining three assigned to the control group. Both groups were pre-tested. The results were equal. After 3 sessions of connected speech lesson both groups were tested again. The post-test results of these two groups were then compared to see if the sample means were significantly different. As the study also aimed to find out the students’ perception towards the teaching practice implemented, a questionnaire was employed. The t-test showed that the difference of the sample means was not significantly large. Nevertheless, based on the feedbacks that were elicited through the questionnaire, the use of songs for teaching the English connected speech seemed to remain promising. Overall, the study showed that the use of songs for teaching the English connected speech tended to indicate a prospective better learning outcome. As the experiment took only 3 sessions, the chance for such treatment to be effective is increased if period of study is extended.